Changes in Seed Quality and Longevity in Soybean due to Storage and Aging - VR SHELAR; AP KARJULE; KC GAGARE (Seed Research, 2026)
Germination and vigour potential of soybean seed is short lived as compared to other grain crop and is often reduced prior to sowing. Hence knowledge of status of seed vigour and viability (longevity) is essential for sequential disposal of seed lots. An experiment was conducted to study the effect of aging and storage on storability and quality of soybean seed. The seed quality parameters viz., germination, vigour index I & II and electrical conductivity of four seed lots of soybean were recorded. The lots were stored at ambient conditions for six months and after every two months of storage, seed quality was observed. Accelerated aging (AA) test of these lots was performed at 48, 96, 144 and 192 hrs for assessing the seed longevity. Pooled analysis of three year data for five characters showed significant differences. Initially the germination of soybean seed was 87%, which was reduced to 82, 77 and 74% after 2, 4 and 6 months of storage, respectively. Germination status of soybean seed after 48, 96, 144 and 192 hrs of AA tests was 79, 72, 39 & 24 % respectively. Seed germination deteriorated more than 50% of initial level of germination after 144 hrs of AA test. Pooled analysis of three year data revealed that germination status observed at 96 hrs of AA test (72%) simulates 6 months storage period (74%) under ambient conditions. Positive and highly significant correlation between these parameters (0.996) indicated close association. Field emergence was also significantly correlated with first count germination (0.957), seedling dry weight and vigour index (0.890).